Sanksi Pidana Pelaku Jual Beli Kendaraan Hasil Curian Dalam Pasal 480 KUHP Perspektif Hukum Pidana Islam - Rayhan Maulana Muhamad; Didi Sumardi; Deden Najmudin (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Motor vehicle theft remains a prevalent property crime in Indonesia, with stolen goods often distributed through third parties acting as sellers or receivers (penadah). Under Article 480 of the Indonesian Penal Code (KUHP), such acts constitute the offense of receiving stolen goods, punishable by up to four years’ imprisonment or a fine of nine hundred rupiahs. In Islamic criminal law, selling stolen goods is haram and classified as jarimah ta’zir, with sanctions determined by the ruler (ulil amri) for public benefit. This study analyzes sanctions against sellers of stolen motor vehicles from the perspectives of Article 480 KUHP and Islamic criminal law, and examines their relevance. Using normative legal research with statutory, conceptual, and comparative approaches, the study draws on primary, secondary, and tertiary legal sources. The findings show that, despite different philosophical foundations, both legal systems aim to protect property (hifz al-mal) and maintain public order. Their relevance lies in similar sanctions—primarily imprisonment and the authority of judges or the government to impose punishments proportionate to the offense’s severity and societal impact.